[PP.25.27] REFRACTORY HYPERTENSION: PREVALENCE, ASSOCIATED FACTORS AND DIFFERENCES WITH RESISTANT HYPERTENSION. (September 2017) - Armario, P.; Oliveras, A.; Blanch, P.; Vinyoles, E.; Banegas, Jr; Gorostidi, M.; Segura, J.; Ruilope, L.M.; Sierra, A. De La
Abstract : Objective: The term refractory hypertension has been recently proposed for a small group of patients with uncontrolled hypertension despite the simultaneous use of >=5 different drug classes. To assess the prevalence of true refractory hypertension and their associated factors in comparison with resistant hypertension. Design and method: The present analysis was conducted from the Spanish Ambulatory Blood pressure monitoring (ABPM) Registry database containing 70997 treated patients who had enough information regarding office BP measurements, ABPM of good quality and complete clinical information. Blood pressure was measured at the office with a validate oscillometric device after 5-minute rest in a sitting position, and office BP estimated as the mean of 2 readings. 24h-ABPM was performed using the Spacelabs 90207 automated non-invasive oscillometric device, programmed to register BP at 20 minutes interval for the 24-hour period. Results: A total of 11.972 (16.9%) patients fulfilled the standard criteria of resistant hypertension (Office BP >= 140 and/or 90 mm Hg) despite the use of >=3 antihypertensive drugs, and 955 (1.35%) were considered as having refractory hypertension (elevated office BP despite the simultaneous use of >=5 antihypertensive agents). The prevalence of white coat (24-hour BP < 130/80 mm Hg) refractory hypertension was lower than white-coat resistant hypertension (26.7% vs 37.1%, p < 0, 0001. Compared with resistant hypertension, patients with refractory hypertension had a significantly higher prevalence of diabetes mellitus (48.1% vs 33.5%; p < 0.001), and obesity (59.6% vs 51.4%; p < 0.001), and a longer duration of hypertension (13.9 vs 10.9 years; p < 0.0001). The prevalence of microalbuminuria (38.5% vs 24.5%; p < 0.0001), ECG-left ventricular hypertrophy(27.6% vs 14.9%; p < 0.0001), and previous history of a cardiovascular event (20.5% vs 14.9%;p < 0.0001) were also significantly higher in refractory, compared to resistant hypertension. Conclusions: The prevalence of refractory hypertension is low. Compared with resistant hypertension, patients with refractory hypertension have more frequently target organ damage, a higher prevalence of diabetes and a longer duration of hypertension.